2006
DOI: 10.1149/1.2178651
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electrical Bias Stress on the Performance of ZnO-Based TFTs Fabricated by RF Magnetron Sputtering

Abstract: ZnO-based thin film transistors ͑TFTs͒ were fabricated on a SiN x /indium tin oxide ͑ITO͒/glass substrate by radio frequency ͑rf͒ magnetron sputtering at 350°C. The transfer characteristics of the fabricated TFT showed a drain current on/off ratio of 10 5 , a field effect mobility of 1.698 cm 2 /Vs, an off current lower than 8 nA, and a threshold voltage of 2.5 V. The stability of the ZnO TFTs was examined under various electrical bias stress conditions. The operation of ZnO TFT was stable at the electrical bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 22 publications
0
33
0
Order By: Relevance
“…Silicon nitride is a promising material to be used as an insulator matrix in metal/ceramic granular systems and multilayers, and it has been proposed for applications in electronic devices due to its transport and optical properties and chemical inertness at high temperatures. [24][25][26][27] However, to our knowledge, not much has been reported about Fe/ Si 3 N 4 systems to obtain multilayered and granular magnetic materials. Structural characterization, prior to the analysis of the magnetic properties, has been achieved by using x-ray and transmission electron microscopy ͑TEM͒ techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon nitride is a promising material to be used as an insulator matrix in metal/ceramic granular systems and multilayers, and it has been proposed for applications in electronic devices due to its transport and optical properties and chemical inertness at high temperatures. [24][25][26][27] However, to our knowledge, not much has been reported about Fe/ Si 3 N 4 systems to obtain multilayered and granular magnetic materials. Structural characterization, prior to the analysis of the magnetic properties, has been achieved by using x-ray and transmission electron microscopy ͑TEM͒ techniques.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Several studies on bias-induced instabilities in ZnO-based TFTs have reported the deterioration of the current-voltage characteristics. [23][24][25] This effect could be manifested as a change in the field-effect mobility, a change in the subthreshold slope, or a shift in the V th voltage. Although the topic of ZnO-based TFTs has aroused growing interest over the past few years, effective approaches to solve this problem, including the development of new compensation circuits for AMOLED displays, [26,27] have not been forthcoming in the literature.…”
mentioning
confidence: 99%
“…Although the on/off ratio and S.S. of our top-gate transparent ZnO TFT appeared to be not very good, its device stability was outstanding, mainly because this top-gate structure does not allow sputtering-induced damage on the dielectric surface unlike the bottom-gate TFT. [14,[29][30][31] Figure 4e and f displays the drain current-voltage (I D -V D ) output curves obtained from the p-channel (pentacene) and n-channel (ZnO) TFTs, respectively, as prepared on nanohybrid dielectric layers. The www.afm-journal.de saturation currents of 0.28 and 0.80 mA were achieved from pentacene-and ZnO-based devices, respectively, under a V G of À3 V for the former and 3 V for the latter.…”
Section: Channelmentioning
confidence: 99%